Comparison of two methods for dimethylarginines quantification - Sudová, Vendula; Prokop, Pavel; Trefil, Ladislav; Racek, Jaroslav; Rajdl, Daniel (Practical laboratory medicine, 2024)
OBJECTIVES: Both dimethylarginines are widely bound to chronic kidney disease (CKD). This study was focused to validate published LC-MS/MS method and compared the measured data with an immunoassay. DESIGN AND METHODS: The analysis was performed on a Dionex UltiMate 3000 UHPLC-Standard (Thermo Fisher Scientific, Waltham, Massachusetts, USA) with an amaZon SL ion trap (Bruker, Billerica, Massachusetts, USA). Comparison was evaluated by using Passing Bablok regression and Bland Altman plot. Healthy volunteers (n = 40) were used for validation and as control group to patients group (n = 40) with different stages of CKD. RESULTS: The results in healthy controls determined by the LC-MS/MS (ELISA) method were 0.52 ± 0.0892 with 95 % CI: 0.49-0.55 (0.61 ± 0.1213 with 95 % CI: 0.57-0.64) μmol/L for AD MA and 0.56 ± 0.0810 with 95 % CI: 0.53-0.58 (0.62 ± 0.0752 with 95 % CI: 0.57-0.65) μmol/L for SDMA. In the same way, the patient group values determined by the LC-MS/MS (ELISA) method were 0.82 ± 0.1604 with 95 % CI: 0.75-0.88 (1.06 ± 0.3002 with 95 % CI: 0.94-1.19) μmol/L and 2.14 ± 0.8778 with 95 % CI: 1.47-2.58 (1.65 ± 0.5160 with 95 % CI: 1.40-1.98) μmol/L for ADMA and SDMA, respectively. The correlation between the methods, expressed as the Spearman correlation coefficient (R), was 0.858 (0.8059) for ADMA (p < 0.0001) and 0.895 (0.9607) for SDMA (p < 0.0001). CONCLUSIONS: ADMA levels determined by the immunoassay were almost 30 % overestimated, in contrast to SDMA levels, which were 3 % underestimated. According to our findings, a better correlation could be obtained by simple sample dilution.
Keywords: LC-MS/MS; ELISA; CKD; Symmetric dimethylarginine; Asymmetric dimethylarginine